Competition, Labor Intensity, and Specialization: Structural Changes in Postcrisis Asia - Yothin Jinjarak; Kanda Naknoi (Asian Development Bank (ADB), 2011)
This study documents empirical regularities related to structural changes in the exporting pattern and degree of competitiveness in selected Asian countries in the decade following the 1997 Asian crisis. We conceptually illustrate that the degree of competitiveness is determined by foreign–domestic wage inflation differentials, changes in the relative cost of capital, growth rate of total factor productivity, and foreign–domestic inflation differentials in the import sector. The contribution of these factors to the degree of competitiveness crucially depends on labor intensity and consumption expenditure shares. Hence, rising wage inflation may not result in a loss of competiveness if it occurs in the sectors in which labor intensity is low and the consumption expenditure share is small. We confirm this prediction using data of 98 industries in nine Asian countries. Specifically, although we found that the exporting pattern in Asia and the degree of competitiveness of Asian economies substantially changed, these structural changes were not caused by labor intensity and wage inflation. However, due to data limitation, we cannot conclude whether these structural changes come from changes of the cost of capital or changes in total factor productivity.
hdl:11540/1992
Keywords: 330; Standortwettbewerb; Arbeitsintensität; Internationale Arbeitsteilung; Strukturwandel; Produktivität; Asien